Performance Enhancement of Organic Solar Cells via Device Engineering and Their Future Potential Applications - Fanady, Billy (2021)
Renewable energy sources are promising long-term solution to solve the energy supply crisis due to the excessive use of non-renewable fossil fuels. One of the options is solar energy, which can be harvested directly from sunlight using photovoltaic (PV) technology. In recent years, organic solar cells (OSCs) as the building blocks of organic PV technology have emerged in the PV field, enabling the realization of environmental-friendly and low-cost PV technology. However, issues related to efficiency performance still posed a major setback to commercialization of OSCs. In view of this, this study is conducted to present comprehensive understandings on how OSCs’ performance in terms of optical, electrical, morphological and mechanical properties can be improved through device engineering strategy (interface and electrode engineering strategy). In addition, the potential applications of OSCs achieved via device engineering strategy are also being explored. In summary, the studies conducted can be divided into three main parts. The first part focuses on improving OSCs’ performance through interface engineering strategy for the realization of high-performing OSCs. Interface engineering on sol-gel zinc oxide (ZnO) electron-transporting layer (ETL) was conducted by introducing additional oxadiazole-based electron-transporting material called 2-(4-tert-butylphenyl)-5-(4-biphenylyl)-1,3,4-oxadiazole (PBD) between ZnO ETL and photoactive layer. The significance of incorporating PBD on ZnO was demonstrated by investigating the change in optical, electrical and morphological properties of pristine ZnO ETL. The findings shown that additional PBD layer could improve pristine ZnO film’s conductivity, create better energy level alignment with the photoactive layer, smoothen ZnO film’s morphology and improve ZnO film’s hydrophobicity. All those factors crucially influenced the charge extraction, transport and recombination processes in OSCs, which were conducive for the enhancement in photovoltaic performance of ZnO/PBD-based device. In fact, through interface engineering strategy, inverted OSCs based on poly[(2,6-(4,8-bis(5-(2-ethylhexyl)thiophen-2-yl)-benzo[1,2-b:4,5-b’]dithiophene))-alt-(5,5-(1’,3’-di-2-thienyl-5’,7’-bis(2-ethylhexyl)benzo[1’,2’-c:4’,5’-c’]dithiophene-4,8-dione)] (PBDB-T donor) and 3,9-bis(2-methylene-((3-(1,1-dicyanomethylene)-6/7-methyl)-indanone))-5,5,11,11-tetrakis(4-hexylphenyl)-dithieno[2,3-d:2’,3’-d’]-s-indaceno[1,2-b:5,6-b’]dithiophene (IT-M acceptor) could demonstrate ~7% increment in the photovoltaic performance from 10.8% (ZnO-based device) to 11.6% (ZnO/PBD-based device). The second part focuses on improving OSCs’ performance through electrode engineering strategy for the realization of high-performing flexible OSCs. Electrode engineering on poly(3,4-ethylenedioxythiophene)-poly(styrenesulfonate) (PEDOT:PSS) electrode was conducted by utilizing polyhydroxy compound dopant and gentle acid post-treatment method, specifically xylitol dopant and methanesulfonic acid (MSA) treatment. The significance of xylitol dopant and MSA treatment on PEDOT:PSS electrode was demonstrated by investigating the change in optical, electrical, morphological and mechanical properties of pristine PEDOT:PSS electrode. The findings shown that both doping and acid treatment on PEDOT:PSS electrode could improve the optical transparency of electrode, enhance electrode’s conductivity and modify electrode’s morphology. In addition, such treatment could also provide electrode a stronger adhesion ability with the substrate, which were effective for improving the mechanical stability of electrode against extreme mechanical deformation. All those factors promoted the realization of high-performing flexible OSCs based on PEDOT:PSS electrode. In fact, through electrode engineering strategy, conventional OSCs based on poly[(2,6-(4,8-bis(5-(2-ethylhexyl-3-fluoro)thiophen-2-yl)-benzo[1,2-b:4,5-b’]dithiophene))-alt-(5,5-(1’,3’-di-2-thienyl-5’,7’-bis(2-ethylhexyl)benzo[1’,2’-c:4’,5’-c’]dithiophene-4,8-dione)] (PBDB-T-2F/PM6 donor) and 2,2'-((2Z,2'Z)-((12,13-bis(2-ethylhexyl)-3,9-diundecyl-12,13-dihydro-[1,2,5]thiadiazolo[3,4-e]thieno[2",3’':4’,5']thieno[2',3':4,5]pyrrolo[3,2-g]thieno[2',3':4,5]thieno[3,2-b]indole-2,10-diyl)bis(methanylylidene))bis(5,6-difluoro-3-oxo-2,3-dihydro-1H-indene-2,1-diylidene))dimalononitrile (BTP-4F/Y6 acceptor) could demonstrate an excellent photovoltaic performance of 14.2% with remarkable mechanical robustness against bending and folding. The last part focuses on the application of device engineering, specifically electrode engineering as a continuation of study from the previous part. The desirable mechanical and optical properties of the engineered PEDOT:PSS could make PEDOT:PSS a great candidate for usage in foldable-flexible semi-transparent OSCs (FST-OSCs). FST-OSCs were fabricated similarly using engineered PEDOT:PSS electrode and PBDB-T-2F:Y6 photoactive layer system. As a result, high-performing FST-OSCs with over 10% efficiency and 21% average visible light transmittance, as well as excellent mechanical stability were obtained. The potential of such FST-OSCs for greenhouse application was investigated by incorporating them as part of roofs in the simulated greenhouse. Comparisons between plants grown under direct sunlight with FST-OSCs roof and those under direct sunlight yielded remarkably similar results in terms of branch sturdiness and hypertrophic leaves, proving the significance of electrode engineering strategy in realizing high-performing FST-OSCs for practical greenhouse applications.